Viability of Agrobacterium sp. I26 and Agrobacterium sp. I30 in The Carrier Formula of Mocaf Solid Waste, Peat and Manure - Rosariastuti, Retno; Nur Sabilla, Widya Putri; Sudadi, Sudadi; Dewi, Widyatmani Sih (ENVIRO: Journal of Tropical Environmental Research, 2022)
Agrobacterium sp. I26 and Agrobacterium sp. I30 are bioremediation agent that can be used as functional bacteria in biofertilizers. The storage of these bacteria requires carrier. Not all carriers can support bacterial viability, so it was necessary to examine carrier formulas as basic ingredients for biofertilizers which the quality standards based on the Minister of Agriculture Regulation No. 70/2011. This research aimed to: (1) study the viability of Agrobacterium sp. I26 and Agrobacterium sp. I30 in some carrier formulas; and (2) obtain the best carrier formula to support the viability of Agrobacterium sp. I26 and Agrobacterium sp. I30. Research design was factorial using completely randomized design (CRD) as the based design, consisting of 2 factors: 1) Carrier Fornula (C): C1; C2; C3; C4; C5, 2) Bacteria (I): I1; I2; I3, so there were 15 treatment combinations each was repeated 4 times, thus there were 60 experimental units. The results showed that Agrobacterium sp. I26 has better viability than Agrobacterium sp. I30 during 90 days incubation period. The best bacterial viability with total bacterial as the indicator was C4 carrier formula: 74 x 1013 cfu.g-1 for Agrobacterium sp. I26 and C3 carrier formula: 155 x 1012 cfu.g-1.